Unlocking optimism in everyday life: a short-term study on the power of live comedy to reduce stress and anxiety in general public - Toshiko Tomisawa; Kayo Horie; Naoya In; Naoki Nanashima; Shizuka Takamagi; Kasumi Mikami (Health Psychology and Behavioral Medicine)
Background Although there have been many studies on laughter and health, few studies have clarified the effects of laughter on optimism and pessimism, as well as anxiety. The purpose of the study was to evaluate the effects of viewing a comedy live performance on optimism, pessimism, and anxiety, sAA as a stress marker, and examine the relationship between laughter attitude and optimism, pessimism and stress marker and clarify significant factors that contribute to optimism.Methods In this pre – post study, we evaluated the effects on attendees of laughter elicited by a comedy live performance (CLP). The participants were 110 volunteers aged 18–64 years. Participants attended a two-hour CLP by four famous Japanese comedians (Sisonnu, Tonikaku Akarui Yasumura, Mouchugakusei, and Panther) and completed pre – and post-event questionnaires that included items from the Japanese Optimism and Pessimism Scale (JOPS), State-Trait Anxiety Inventory (STAI), the Laughter Attitude Scale (LAS) and Salivary alpha-amylase (sAA).Results The valid response rate was 101. Participants’ optimism was higher, and pessimism, anxiety and sAA were lower, after attending the CLP. α-amylase was significantly lower in more people before and after CLP. Factors contributing to optimism were strongly influenced by the degree to which people made them laugh, as well as pessimism, anxiety, and forced laughter.Conclusion The personal factors contributing most strongly to optimism were ‘A state that makes you laugh,’ as well as pessimism, anxiety, and a low level of ‘Forced Laughter.’ Attending a two-hour CLP increased optimism and decreased stress level, pessimism and anxiety, these effects were more pronounced in those who laughed regularly in their everyday lives.